Does Curriculum Fail Indigenous Political Aspirations? Sovereignty and Australian History and Social Studies Curriculum - Keynes, Mati; Marsden, Beth; Thomas, Archie (Umeå University Library, 2023)
Through analysis of curricular materials (syllabus documents and supplementary readers) from the late-nineteenth century to the present, this article explores the role of school curriculum in shaping understandings of Indigenous political aspirations in the Australian context. It juxtaposes curricular materials with significant occasions of Indigenous political activism in Australia since the late-nineteenth century: the Coranderrk campaign of the 1870-80s, the Wave Hill Walk Off in 1966, the establishment of the Aboriginal Tent Embassy in 1972, and the Bicentenary protests of 1988. From this analysis, five narrative sub-themes were developed—Invisibility, Benevolence, Obfuscation, Innocence, and Acknowledgement—which captured the ways that Indigenous sovereignty, nationhood, and political legitimacy had been represented. In drawing out some continuities and changes to curricular representations of First Nations’ and settler sovereignty, nationhood, and political legitimacy over a one hundred year period, this article highlights the uneven ways that curriculum has, and continues to, represent political possibilities on the Australian continent. This article offers insights for Nordic contexts where there are also contests about legacies of colonialism in the public sphere, including in education.